2022
DOI: 10.3390/f13070994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest on Birdsong and Human Acoustic Perception in Urban Parks: A Case Study in Nigeria

Abstract: The quality of the natural sound environment is important for the well-being of humans and for urban sustainability. Therefore, it is important to study how the soundscape of the natural environment affects humans with respect to the different densities of vegetation, and how this affects the frequency of singing events and the sound pressure levels of common birds that generate natural sounds in a commonly visited urban park in Abuja, Nigeria. This study involves the recording of birdsongs, the measurement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The envelopment of vegetation reduces the influence of coastal tidal winds, facilitating the rapid settling of airborne particles. The physical and chemical properties of vegetation, including leaves and stems, accelerate the adhesion of airborne particles, resulting in lower concentrations of airborne particles in closed and partially enclosed spaces [48]. Moreover, existing research suggests a correlation between vegetation density and noise attenuation [49].…”
Section: Differences In Health Effects Of a Single Recuperative Facto...mentioning
confidence: 99%
“…The envelopment of vegetation reduces the influence of coastal tidal winds, facilitating the rapid settling of airborne particles. The physical and chemical properties of vegetation, including leaves and stems, accelerate the adhesion of airborne particles, resulting in lower concentrations of airborne particles in closed and partially enclosed spaces [48]. Moreover, existing research suggests a correlation between vegetation density and noise attenuation [49].…”
Section: Differences In Health Effects Of a Single Recuperative Facto...mentioning
confidence: 99%
“…They found that the power spectral density (PSD) and the soundscape diversity index (SDI) of the park were greatly affected by public recreation behaviors. Nwankwo et al [16] explored how the soundscape of the natural environment could affect humans with respect to the different densities of vegetation, as well as the frequency of singing events and the sound pressure levels of common birds that generate natural sounds in a commonly visited urban park. Chen et al [17] explored the spatial dependency of the soundscapes in Kulangsu, based on the spatiotemporal dynamics of soundscape and landscape perceptions.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%
“…The perception of soundscapes is closely related to the characteristics of the environment, time, and space in which people live [17][18][19]. Urban forest parks are usually Forests 2023, 14, 1435 2 of 13 natural spaces adjacent to cities and connected to residential areas [20,21].…”
Section: Introductionmentioning
confidence: 99%